Embroidering plants and flowers for beginners : 33 plants to stich - Pourias, Charlène (Landauer Publishing, 2023)
"An embroidery guide for all skills levels with overviews on tools, supplies, and techniques, plus over 30 embroidery designs for flowers, herbs, plants, and more"--